DEVELOPMENT A PROGRAM TO ENHANCE TEACHER’S INNOVATIVE AND TECHNOLOGIES DESIGN FOR LEARNING OF SCHOOL UNDER THE OFFICE OF CHAIYAPHUM PRIMARY EDUCATIONAL SERVICE AREA 3 - Veeranarong, Wongsathor; Chittranun, Thatchai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research the objectives are 1) to study the current condition Desirable conditions and necessities of teacher development in innovative design and technology for learning management in educational institutions. Under the Office of Chaiyaphum Primary Educational Service Area 3 2) To develop a teacher development program on innovative design and technology for learning management in educational institutions Under the Office of Chaiyaphum Primary Education Service Area 3, the sample group consisted of 310 teachers, 3 schools with excellent practice, and 5 qualified experts assessing the suitability and feasibility of the program. The research uses were questionnaires, semi-structured interviews. Program feasibility and feasibility assessment form. The statistics used in the data analysis were percentage, mean, standard deviation. Conformity Index Value Pearson’s correlation coefficient Cronbach’s Alpha Coefficient and the need to prioritize the index value The results of the research were as follows: 1. The current state of innovative design and technology for learning management in educational institutions. Under the Office of Chaiyaphum Primary Educational Service Area 3, the overall level was at a high level. and desirable conditions in innovative design and technology for learning management in educational institutions Under the Office of Chaiyaphum Elementary Education Service Area 3, the overall level was at the highest level. 2. Teacher development program in innovative design and technology for learning management in educational institutions under the Office of Chaiyaphum Elementary Education Service Area 3 consist of: 1) Principles 2) Objectives 3) Content is divided into 5 modules and teacher development method, model 70:20:10. The development method consists of meetings, workshops. follow-up supervision learning from practice and self-study 4) program process 5) evaluation results of assessment of the feasibility and feasibility of the overall program It is appropriate and feasibility is at a high level.